IT Governance with Framework Implementation Cobit 5 at Yapim Air Bersih Senior High School Medan - Harahap, Lelyana; Panggabean, Jonas Franky R; Sirait, Kamson; Purba, Sartika Dewi (Jurnal ICT : Information and Communication Technologies, 2025)
Technology information is very important thing nowadays in help the search process correct information . At SMA YAPIM Air Bersih Medan still use technology information that is still simple in give service to users , so that make it difficult in access information . Therefore That needed A analysis that can help finish problem that is one of technology analysis that can done with using the Cobit framework . Cobit or Control Objectives for Information and related Technology are framework used in governance analysis technology information . There are 3 things analysis according to Cobit shared namely the DSS, APO and MEA domains. Safira et al., (2021) in his research titled Technology Governance Analysis Information Use Cobit 5 (Case Study: Head Office By Banana Foster Lampung) which discusses about evaluation technology information that has been applied to the company with using the COBIT 5 framework with the APO08 (Manage Relationship) domain. The existing problems that is system constraints information called GF which functions For arrange sales , stock and accounting turnover that is GF system used Enough Far so that response If happen problem Enough slow . Based on results evaluation governance analysis technology Information on YAPIM Air Bersih Medan High School , Implementation of IT governance during the IT work process at YAPIM Air Bersih Medan High School which includes the MEA01, APO09 and DSS02 domains has been done with good . Capability level moment This is at level 4 ( Predictable ). Namely range in value achievement of 4 and required development documents related with the process domain being studied as well as improvement amount source power that manages technology information at the Yapim Air Bersih High School Medan.